Formulation Development, Physicochemical Characterization and In Vitro-In Vivo Drug Release of Vaginal Films - Ghosal, Kajal; Hazra, Bipad Taran; Bhowmik, Benoy Brata; Thomas, Sabu (Current HIV research, 2016)
PURPOSE: The purpose of this study was formulation and optimization of vaginal film formulation containing abacavir (ABC), a potent nucleoside reverse transcriptase inhibitor. METHODS: Vaginal films were prepared by solvent evaporation method using hydroxypropyl methylcellulose (HPMC) blended with polyvinyl pyrrolidone (PVP). Various physicochemical parameters of the prepared films such as drug content, thickness, tensile strength, percentage elongation at break, drug polymer interaction, swelling capacity, folding endurance, bio-adhesion, pH, and moisture content were evaluated with morphological studies. In vitro release study and in vivo release study were also performed. RESULTS: Films exhibited favorable physicochemical properties. The in vitro study showed that HPMC-PVP combination can control the release of abacavir through vaginal films with higher amount of PVP in the formulation resulting in an enhanced drug release rate. During the in vivo study in rabbits, systemic absorption of the drug was noted and the films remained intact for long in vagina without causing any sort of irritations. CONCLUSION: Thus, in a nutshell, the findings of our experimental work indicate that such films can be considered as a novel drug carrier system for the treatment of AIDS and other sexually transmitted diseases (STDs), and are suitable for local as well as systemic effects.
Keywords: Dosage Forms; látky proti HIV; dideoxynukleosidy; lékové formy; aplikace intravaginální; chemické jevy; Dideoxynucleosides; Drug Carriers; Chemical Phenomena; králíci; Animals; ženské pohlaví; Administration, Intravaginal; Drug Compounding; zvířata; Drug Liberation; Rabbits; příprava léků; uvolňování léčiv; Anti-HIV Agents; nosiče léků; Female